(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
This article reveals the impact of technology on teaching English, and shows how technology can help the process teaching and learning. The aim of the article is to show the importance of technology and to present the main points of teaching with technology. The use of technology has become an important of the learning process. Every language class usually uses some form of technology. Technology continues to help teachers facilitate language learning for their learners. Teachers should use educational innovative tools as projector, electronic whiteboards, Virtual Field Trips in order to explain more effectively end get satisfying results from learners. Using these tools help to enhance students ‘language skills, because it has a crucial role in developing their creativity and provides them with interesting, enjoyable and exciting alternatives to study the language